What church people think about social and economic issues. Report of an opinion survey made in Baltimore under the Baltimore Rauschenbusch Fellowship of the Council of Churches and Christian Education of Maryland and Delaware. Introd. by F.E. Johnson (Association Press, 1938)
With bibliogr.